Numerical-analytic method for the investigation of multipoint boundary-value problems for systems of differential equations with transformed argument - Bigun, Ya. I.; Filipchuk, M. P. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
The problem of existence and approximate construction is studied for the solution of a nonlinear system of differential equations with a transformed argument and linear multipoint boundary conditions.